Model Kebijakan Pendidikan Islam dalam Perspektif Komparatif: Analisis Sistem Pendidikan di Malaysia, Turki, Mesir, dan Negara-Negara Barat - Anton Sulistio; Usman Usman; Nor Fadhilah (STIKes Ibnu Sina Ajibarang, 2026)
Islamic education in various developing countries takes shape within policy frameworks influenced by demographic characteristics, political systems, and national educational orientations. Although numerous studies have examined Islamic education policies in specific countries, comparative studies that map the relationships between demographic characteristics, educational systems, and policy models remain relatively limited. This study aims to analyze and map models of Islamic education policy in Malaysia, Turkey, Egypt, and Western countries to identify patterns, characteristics, and the dynamics of policy development in each context. The study employs a qualitative approach using library research. Data were obtained from academic books, journal articles, and policy documents, and were analyzed using content analysis through a comparative approach. The results reveal four main typologies of Islamic education policies: the integrative-centralized model (Malaysia), the hybridization-negotiation model (Turkey), the dualism-convergence model (Egypt), and the multicultural adaptation model (Western countries). This study also found that the diversity of these policies is not merely a consequence of state dominance but reflects a process of creative friction between state interests, religious identity, and the demands of globalization, which drives institutional transformation and innovation in Islamic education. These findings lead to the conceptual perspective that the future of Islamic education policy should be directed toward Islamic Cosmopolitanism an educational paradigm that combines the strengthening of Islamic scholarly traditions with global leadership capabilities thereby producing human resources who are religious, adaptive, inclusive, and competitive in this era of disruption.